A conceptual framework for the Basel accords-based regulation. Issue 1 (8th February 2016) - Mohammed Ahmed, Jaffar
Abstract : Purpose: – The purpose of this paper is to describe a theoretical model for banking regulation in relation to Basel accords implementation. As a risk manager practitioner at a financial institution and in-charge of Basel implementation in a Basel accords environment of banking regulation, the author has been intrigued by the theoretical basis of the design of Basel accords. The objective was to investigate a theoretical model in the literature according to which the accords were designed. In case of deficiency in the literature of this model, the author seeks to provide a juxtaposition to the theoretical model that explains the accords adoption and implementation by regulators. Design/methodology/approach: – This paper presents a review of existing literature. Findings: – After reviewing of public interest theory, cultural theory, administration theory and the new-institutionalism theory, the author found little application of these theories to the capital-based regulation, particularly in relation to Basel 2 accord. There is deficiency in the literature of a conceptual theoretical framework based on which the author can explain the adoption of Basel accords. The author has provided a theoretical model that links these theories to the practice of banking regulation. This paper found deficiencies in theories of how banks should be regulated as compared to several theories that explains why banks are regulated. Originality/value: – After reviewing of public interest theory, cultural theory, administration theory and the new-institutionalism theory, the author found little application of these theories to the capital-based regulation, particularly in relation to Basel 2 accord. There is deficiency in the literature of a conceptual theoretical framework based on which the author can explain the adoption of Basel accords. The author has provided a theoretical model that links these theories to the practice of banking regulation. This paper found deficiencies in theories of how banks should be regulated as compared to several theories that explains why banks are regulated.